2020
DOI: 10.1016/j.ijantimicag.2020.106191
|View full text |Cite
|
Sign up to set email alerts
|

Projected supportive effects of PycnogenolⓇ in patients suffering from multi-dimensional health impairments after a SARS-CoV2 infection

Abstract: Highlights Review of the symptoms in COVID-19 and Pycnogenol®’s potentially beneficial effects in this disease. COVID-19 patients suffer from inflammation of endothelial cells, microvascular injuries and coagulopathies. Pycnogenol® has proven anti-inflammatory, anti-oxidative, endothelium-protective and platelet activity regulating properties. A supplementation with Pycnogenol® might support the management of COVID-19 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 127 publications
0
12
0
1
Order By: Relevance
“…Several clinical studies with patients having no or particular comorbidities showed that PycnogenolⓇ can improve endothelial function (Enseleit et al, 2012;Nishioka et al, 2007;Weichmann and Rohdewald, 2020;Zibadi et al, 2008). The suggested mechanism of action is activation of the endothelial nitric oxide synthase (eNOS), thus amplifying the NO generation from L-arginine, eventually leading to an increase in vessel lumen and adequate tissue perfusion.…”
Section: Improvement Of Endothelial Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Several clinical studies with patients having no or particular comorbidities showed that PycnogenolⓇ can improve endothelial function (Enseleit et al, 2012;Nishioka et al, 2007;Weichmann and Rohdewald, 2020;Zibadi et al, 2008). The suggested mechanism of action is activation of the endothelial nitric oxide synthase (eNOS), thus amplifying the NO generation from L-arginine, eventually leading to an increase in vessel lumen and adequate tissue perfusion.…”
Section: Improvement Of Endothelial Healthmentioning
confidence: 99%
“…Urinary albumin levels significantly decreased and kidney cortical blood flow increased in patients taking PycnogenolⓇ in addition to an ACE inhibitor, compared with subjects medicated only with the ACE inhibitor for 6 months (Cesarone et al, 2010;Stuard et al, 2010). PycnogenolⓇ has the potential to act favorably and bring microcirculation to normal levels (Weichmann and Rohdewald, 2020).…”
Section: Improvement Of Microcirculationmentioning
confidence: 99%
See 3 more Smart Citations